Pendidikan Anak Usia Dini sebagai Alas Pendidikan - Asef Umar Fakhruddin (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Since early age, children have to give knowledge, in a form of many stimuli. Teaching at early age is like forming carving at stone that will last forever. Early education is a foundation to next education. Therefore, successfulness of early education will have significant role on children successfulness in the future.Â